KEPEMIMPINAN PENATALAYANAN (SERVANT LEADERSHIP) ROHANIWAN (CHAPLAIN) SEKOLAH DALAM MENINGKATKAN NILAI KEUNGGULAN (Studi Kasus di SMP Methodist Sanggau Ledo) - Panjaitan, Krisman; M. Syukri, M. Syukri; Wahyudi, Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Servant leadership realizes and appreciates that he as a servant leader provides life examples. Stewardship leadership influences, controls, coordinates, and leads for one great purpose.The purpose or problem under study is to understand how the leadership of school chaplain stewardship can increase the value of Methodist excellence at SMP Methodist Sanggau Ledo. This form of research uses a descriptive method with a case study approach and type of research. The research subjects were 7 participants. The number of students is 2 people, 1 male and 1 female aged 15 years; male school chaplain 1 person aged 32 years; the principal of the Sanggau Ledo Methodist Junior High School, 1 woman, 34 years old; Parents/community about 1 male aged 59 years. 1 female teacher, 38 years old, 1 Central Chaplain Coordinator. Sampling using snowball sampling, considering the large number of informants. The method used is interviews, direct observation, and retrieval of several documents. Using instruments in research include interview guides/interviews; observation guide; document.The main finding in this study is that the leadership of school chaplain stewardship in increasing the value of excellence at SMP Methodist Sanggau Ledo, is well implemented. It can be seen from the character of school principals and teachers who instill the value of balance in faith and knowledge; self-control; adopt a simple lifestyle; work ethic and spirit of service; lifelong learning. Shown at school or when students are in dormitories. The conclusions of this study are (1) the implementation of the school chaplain stewardship leadership framework in increasing the value of methodist excellence, shows good results. (2) The steps of chaplain stewardship leadership, shown by an attitude of listening, caring, etc. (3) the supporting factors of stewardship leadership are humble, open attitude. The inhibiting factor is the lack of transparency, and mutual respect.The implication of the results of this study is that the involvement of chaplains who lead and influence sincerely and patiently can achieve the goal of excellence value very well..